THEORETICAL FLANGING PRINCIPLES IN ROUND BILLET WITH ITS LOCAL HEATING - L. A. Isaevich; M. I. Sidorenko; А. V. Shimansky; A. N. Sidorenko (Наука и техника)
The paper considers wall thickness changes of a round billet in the pipe expansion process with subsequent flanging owing to thinning of this wall in the strain zone and bearing strain of an internal edge. Equations for calculation of thinning value are given in the paper.